Comprehensive Review of Laboratory Science and its Impact on Medical Diagnostics - Alharbi, Fadiyah Ahmed Ibrahim; Almarwani, Adel Obaid Hmadan; Aljohani, ABDULRAHMAN Abdullah Atallah; Alomari, Abdulhadi obidallah Mater; Alalwani, Yousef Eid Salem; Alnashri, Fahad Mohammed Hussin; Alenezi, Abdulaziz Zaal F; Al. balwi, Salem Saleh Farasan; Alalwani, Mohammaed Eid Salem; Zuayr, Ahmed Abdulrahman (Journal of Ecohumanism, 2024)
The development of molecular bioscience and diagnostic laboratories is the key to current healthcare schemes and patient management. Increased improvements in laboratory technologies such as molecular diagnostics, immunoassay, and automated laboratory systems have improved negativity, shortened the turnaround time, and facilitated early disease diagnosis. This extensive analysis assesses the historical development and contemporary stances of laboratory science, diagnostic technologies, and the role of laboratory tests in present-day medical practice. Also, problems like the test's accuracy, the cost of the test, and the incorporation of laboratory information into clinical practice are addressed. This review then provides recommendations that can enhance laboratory services' operations and their interaction with health systems for the benefit of patients.